Answer:
This is nonlinear.
Step-by-step explanation:
Can you tell us what the expression is in the question?
Answer = 5.656854249
Step by step:
This equation is just a simple Pythagorean theorem ( if you were not aware, it’s a2 + b2 = c2. To get c is to find the square root of c)
Answer:
yes
Step-by-step explanation:
4:8 and 3:6 when simplified gives the same result which is 1:2
Answer:
-18
Step-by-step explanation:
((-3)2)3
First, you multiply -3 and 2 which equals -6
-3·2=-6
Then, you multiply -6 and 3 which equals -18
-6·3=-18